Taking on the Commercial Determinants of Health at the level of actors, practices and systems - Jennifer Lacy-Nichols; Alexandra Jones; Kent Buse (Frontiers Media S.A., 2023)
Tackling the Commercial Determinants of Health (CDoH) is necessary for progress on health equity and will determine whether or not the health-related targets of the SDGs are met. We present a simple visual heuristic of three core aspects of CDoH: commercial actors, commercial practices, and system-level dynamics (which commercial actors influence and perpetuate). We use this heuristic to highlight key research gaps, in particular the need for more voices and evidence on CDoH from the Global South, particularly on what works to curb harmful impacts. We also propose an agenda to address CDoH and actions for different stakeholders. While efforts to curb specific commercial practices are important, far more attention and effort are needed at the systems level, as they can fundamentally shift the way power is distributed in society to improve health equity.